Multinational corporations and the EU emissions trading system: Asset erosion and creeping deindustrialization? - Nils aus dem Moore; Philipp Großkurth; Michael Themann (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
This study investigates the causal effect of the EU Emissions Trading System (EU ETS) on firms' holdings of fixed assets as an early indicator of industrial relocation, exploiting installation level inclusion criteria of the regulation. To single out companies with particularly low relocation costs, global multinational enterprises (MNEs), we identify ownership structures for the full sample of EU ETS-firms. Matched difference-indifferences estimates provide robust evidence that contradicts the idea of an erosion of European asset bases. Baseline results indicate that the EU ETS led on average to an increase of treated firms' asset bases of 11,1%. However, for a particular subgroup of MNEs, this increase is a mere 1.3%. For these companies, the EU ETS may have induced a shift in investment priorities. While the positive overall effect is very robust, the differential effect for the subgroup cannot be extended to all samples.
Keywords: F23; H23; Q54; Q58; C21; 330; EU ETS; cap-and-trade; carbon leakage; multinational corporation